Improving the structural schemes of optical dust measuring instruments - Корнієнко, Дмитро Григорович (Technology audit and production reserves, 2016)
This article describes the structural schemes of the next optical dust measuring instruments: single-channel, dual-channel, fixed, mobile, application features and specifications. The main aim of research is to improve the accuracy of measuring the dust concentration and reduce the measurement error due to the invariant schemes of construction of the optical dust measuring instruments. Use of optical dust measuring instruments is important to monitor the protection of the environment, including health standards, certification of workplaces. It is cause of both periodic and continuous monitoring of the dust concentration with automatic dust measuring instruments that implement different methods of dust measurement in visibility on the operating conditions, operating mode, measuring range, requirements for speed and reliability. The choice of structural construction of dust measuring instruments is proved depending on the range of dust concentration. Proposed Use of invariant schemes for construction of dust measuring instruments: gravimetric and optical with physical equivalents.